EFFECT OF LEADERSHIP STYLES, ORGANIZATIONAL CLIMATE AND ETHOS OF WORK ON EMPLOYEE PRODUCTIVITY (PT. HP METALS INDONESIA THE POWDER COATING) - Nasution, Ade Parlaungan; Mahargiono, Ponco Bambang; Soesatyo, Yoyok (Universitas Riau Kepulauan, 2016)
The aim of this study is to investigate and examine the effect of leadership style on employee productivity, identify and examine the effect of organizational climate on employee productivity, to identify and examine the effect of the work ethic on employee productivity, in order to know and examine the variables that have the most impact level dominant on employee productivity PT. HP Metals Indonesia part Powder Coating.Â This research is an explanatory research or study the explanation, the research describes causal relationships between variables through hypothesis testing. The numbers of sample in this study are 98 respondents. The independent variables consist of: Leadership styles (X1), Organizational Climate (X2), Work Ethics (X3). The dependent variable in this study is Productivity employee (Y). While, the technique of analysis using multiple linear regression analysisÂ Based on the analysis in this study showed that the variables of leadership style, organizational climate, work ethic on employee productivity responded well by employees. Aspects of leadership style that followed targeted Climate employee srated the organization has also been rated as good, especially on the cooperation between employees and management, while at the work ethic of employee srated very high, especially on adherence to regulations, adherence to labor standards and work ethics. And employee productivity is also very positive response from almost all three elements, namely timeliness, quality of work and quantity of work.